OpenStack Swift using, administering, and developing for Swift object storage - Arnold, Joe (O'Reilly Media, 2015)
In this practical guide, Joe Arnold, co-founder and CEO of SwiftStack, brings you up-to-speed on the basic concepts of object storage and walks you through what you need to know to plan, build, operate, and measure the performance of your own Swift storage system.